2017
DOI: 10.3892/or.2017.5755
|View full text |Cite
|
Sign up to set email alerts
|

miR-367 promotes tumor growth by inhibiting FBXW7 in NSCLC

Abstract: Abstract. miR-367 is one of the most abundant miRNAs in human embryonic stem cells (hESCs) and is mainly involved in maintaining the pluripotency of stem cells. However, its role in cancer development remains poorly understood. In the present study, we explored the function and mechanism of the endogenous miR-367 in non-small cell lung cancer (NSCLC). In the present study, we demonstrated that the level of miR-367 in NSCLC was significantly higher than that in adjacent normal tissues, and its upregulation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…FBXW7 was proved to be a tumor suppressor in regulating tumors progression. A study showed that FBXW7 was identified as a potential target of miR-367 in regulating tumor growth of NSCLC [31]. Also, miR-92a mimic promoted the tumor growth of osteosarcoma via suppressing FBXW7 [32].…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 was proved to be a tumor suppressor in regulating tumors progression. A study showed that FBXW7 was identified as a potential target of miR-367 in regulating tumor growth of NSCLC [31]. Also, miR-92a mimic promoted the tumor growth of osteosarcoma via suppressing FBXW7 [32].…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 is a cell cycle protein that regulates the stability of several oncoproteins, including c-Myc, cyclin E, c-Jun, SREBP, Notch, and c-Myb, thereby acting as a vital tumor suppressor gene. 32 Multiple studies have reported that FBXW7 expression is regulated by several miRNAs, such as miR-223, miR-25, miR-182, and miR-367. 32,33 Kurashige et al examined miR-223 and FBXW7 expression levels in 109 pairs of primary EC tissue samples and corresponding normal esophageal epithelium samples obtained from patients who underwent esophageal resection without preoperative treatment.…”
Section: Zn Deficiency Affects the Development Of Ec By Regulating MImentioning
confidence: 99%
“…32 Multiple studies have reported that FBXW7 expression is regulated by several miRNAs, such as miR-223, miR-25, miR-182, and miR-367. 32,33 Kurashige et al examined miR-223 and FBXW7 expression levels in 109 pairs of primary EC tissue samples and corresponding normal esophageal epithelium samples obtained from patients who underwent esophageal resection without preoperative treatment. The miR-223 expression level was significantly higher in primary cancer tissues than in corresponding normal tissues.…”
Section: Zn Deficiency Affects the Development Of Ec By Regulating MImentioning
confidence: 99%
See 1 more Smart Citation
“…10 MiR-367 exerts a tumor-promoting effect through negatively regulating FBXW7 in non-small cell lung cancer (NSCLC), and it could be a potential therapeutic target for NSCLC intervention. 11 MiR-100 and miR-125b are associated with lymph node metastasis in early colorectal cancer, and may be novel biomarkers for the lymph node metastasis of early colorectal cancers with submucosal invasion. 12 Therefore, studying disease-related miRNAs is helpful for analyzing pathogenesis and exploring the rules related to diseases.…”
Section: Introductionmentioning
confidence: 99%